Whither sub-regional cooperation? The China-clmv trade perspective - Devadason, E.S. (2010)
Recent debates advocate that closer sub-regional trade cooperation may be an excellent start to stronger regional cooperation. The study investigates this proposition for the case of CLMV countries that remain less integrated into the ASEAN region. In this respect, the China-CLMV bilateral trade flows are examined prior to detailing the role of China as a core trade partner to the periphery of CLMV in enhancing trade expansion within the context of intra-ASEAN regional and intra-GMS sub-regional synergies. The key findings of the study are: First, there are negative effects of China-CLMV trade collaboration, whereby the export potential particularly for agricultural products is clearly underexploited. Second, China’ trade relations with CLMV indicate that import integration lags behind export integration. The Chinese import potential of CLMV’s manufactures in particular is underexploited, plausibly reflecting the inability of the latter to be part of the regional supply chain. Third, when China’s regional and sub-regional influence is considered along the dimensions of an export destination, there are positive gains for CLMV and the magnitude of those gains appear larger within the sub-regional context. Overall, the study points out that though the China-CLMV trade relations remain sub-optimal as it is unbalanced and underexploited, sub-regional membership of CLMV in the GMS is important as benefits can be derived from the Thailand-China synergy, geographical proximity and common border effects.